1974
DOI: 10.4039/ent106545-5
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF ZECTRAN ON THE PARASITOIDS OF THE SPRUCE BUDWORM, CHORISTONEURA FUMIFERANA (LEPIDOPTERA: TORTRICIDAE)

Abstract: Can. Ent. 106: 545-554 (1974) Where the insecticide Zectran was used to protect foliage from feeding of the spruce budworm, Choristoneura fumiferana (Clemens) (Lepidoptera: Tortricidae), the per cent parasitism of dipteran parasitoids (Tachinidae) showed a statistically significant lower value. In treated areas, the per cent parasitism of the hymenopteran Ephialtes ontario (Cresson) (Ichneumonidae) was lower;Meteorus trachynotus Viereck was about the same; Apanteles fumiferanae Viereck, Glypta fumiferanae (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
3
2
0
Order By: Relevance
“…Egg parasitism by Trichogramma minutum Riley was 2to 7-fold higher in the treated plots than in the untreated check in the year of application. These observations compare favourably with reports by Jaynes and Drooz (1952), Thomas (1966), and Leonard and Simmons (1974) that T. minutum incidence increased in plots treated with Zectran and DDT. Kettela and Varty (1972), however, found no gross differences in T .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Egg parasitism by Trichogramma minutum Riley was 2to 7-fold higher in the treated plots than in the untreated check in the year of application. These observations compare favourably with reports by Jaynes and Drooz (1952), Thomas (1966), and Leonard and Simmons (1974) that T. minutum incidence increased in plots treated with Zectran and DDT. Kettela and Varty (1972), however, found no gross differences in T .…”
Section: Resultssupporting
confidence: 89%
“…The dramatic increased incidence of parasitism in the chemical insecticide-alone plot is enigmatic but apparently not unique. Macdonald (1959), Williams et al (1969), and Leonard and Simmons (1974) have observed higher densities of the spruce budworm larval parasite Apanteles fumiferanae Viereck in areas treated with DDT and Zectran. Macdonald considered it possible that parasitized larvae were less active and less likely to contact residual deposits of the insecticide.…”
Section: Resultsmentioning
confidence: 95%
“…These observations compare favourably with reports by Jaynes and Drooz (1952), Thomas (1966), and Leonard and Simmons (1974) that T. minutum incidence increased in plots treated with Zectran and DDT. These observations compare favourably with reports by Jaynes and Drooz (1952), Thomas (1966), and Leonard and Simmons (1974) that T. minutum incidence increased in plots treated with Zectran and DDT.…”
Section: Resultssupporting
confidence: 89%
“…on the parasitoids per se; rather, they are a function of host response prior to and after spraying. Similar results have been reported by other investigators (Leonard and Simmons 1974;MacDonald 1959;and Williams et al 1969) when the materials Zectrann and DDT were applied. Kettela and Varty (1972) noted that parasitism is an important factor, but not a key one, in the dynamics of epidemic budworm populations.…”
Section: Discussionsupporting
confidence: 91%